Larynx cancers attributable to alcohol consumption in the Republic of Belarus - Sysa, Aliaksei G.; Makarevich, Darya V.; Zhyvitskaya, Alena P. (Journal of the Belarusian State University. Ecology, 2018)
For the larynx cancer there is convincing evidence of a positive association with alcohol consumption. Sex- and cancer-specific population attributable fractions (PAF) were calculated based on: 1) the prevalence of alcohol drinkers among people ≥15 years of age in 2000; 2) the average daily alcohol consumption (g/day) among drinkers in 2000; 3) national cancer incidence data from 2015. Among men, 36,9 % (330 cases) of incident laryngeal cancer cases were attributable to alcohol consumption. Among women, 13,7 % (4 cancer cases) of incident cancers were attributable to alcohol consumption. Avoiding alcohol consumption, or reducing it from the median of the highest 4th quartile of consumption (50.0 g/day for men, 30.0 g/day for women) to the median of the lowest quartile (20.0 g/day for men, 10.0 g/day for women), would reduce the burden of alcohol-related cancers in Belarus. A reduction in alcohol consumption would decrease the cancer burden and a significant impact is anticipated specifically for the larynx cancers among men in the Republic of Belarus.
Keywords: alcohol; larynx cancer; risk factor; population attributable fraction